2014
DOI: 10.4161/rna.28300
|View full text |Cite
|
Sign up to set email alerts
|

miR-499 protects cardiomyocytes from H2O2-induced apoptosis via its effects onPdcd4andPacs2

Abstract: Background microRNAs (miRNAs) are a class of small, non-coding endogenous RNAs that post-transcriptionally regulate some protein-coding genes. miRNAs play an important role in many cardiac pathophysiological processes, including myocardial infarction, cardiac hypertrophy, and heart failure. miR-499, specifically expressed in skeletal muscle and cardiac cells, is differentially regulated and functions in heart development. However, the function of miR-499 in mature heart is poorly understood.Results We report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(64 citation statements)
references
References 43 publications
(54 reference statements)
1
63
0
Order By: Relevance
“…Additionally, miR-499 also exerts an anti-apoptotic effect on cardiac cells induced by H 2 O 2 . Lower levels of miR-499 in the myocardium are associated with decreased cardiac systolic function during reperfusion as compared with levels of other miRNAs [20]. Furthermore, miR-499 levels in the myocardium are negatively correlated with levels of cardiac troponin complex in the peripheral blood, indicating that myocardial levels of miR-499 might reflect the degree of cardiomyocyte damage [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, miR-499 also exerts an anti-apoptotic effect on cardiac cells induced by H 2 O 2 . Lower levels of miR-499 in the myocardium are associated with decreased cardiac systolic function during reperfusion as compared with levels of other miRNAs [20]. Furthermore, miR-499 levels in the myocardium are negatively correlated with levels of cardiac troponin complex in the peripheral blood, indicating that myocardial levels of miR-499 might reflect the degree of cardiomyocyte damage [19].…”
Section: Discussionmentioning
confidence: 99%
“…miR-499 also protects the myocardium against myocardial I/R injury with cardiopulmonary bypass, suggesting that mir-499 may be a potential therapeutic target in cardiac protection during open-heart surgery [19]. Wang et al also demonstrated that miR-499 inhibits the mitochondrial apoptosis pathway and protects cardiomyocytes against H 2 O 2 -induced injury [20]. PDCD4 is an important target gene that protects cardiomyocytes from apoptosis induced by ischemia during ischemic preconditioning [21].…”
Section: Introductionmentioning
confidence: 99%
“…In hepatocellular carcinoma cells, inhibitors of apoptosis (IAPs) target PACS-2 for proteasomal degradation, thereby protecting the cancer cells from being killed by TRAIL (Guicciardi et al, 2014). In cardiomyocytes, miR499 prevents Bid-dependent apoptosis by downregulating PACS-2 (Wang et al, 2014). Not surprisingly, herpesviruses also exploit the ability of PACS-2 to traffic proteins to mitochondria.…”
Section: Introductionmentioning
confidence: 99%
“…miR-499 was found to be expressed in the heart, and circulating miR-499 is suggested to be a sensitive biomarker for acute myocardial infarction [19]. It was also found to protect cardiomyocytes from H 2 O 2 -induced apoptosis by targeting Pdcd4 and Pacs2 [20]. However, no study has explored the role of miR-499 in hepatic insulin resistance.…”
Section: Discussionmentioning
confidence: 99%